INDONESIAN LOW RANK COAL RESOURCES TO WHICH UBC TECHNOLOGY IS COMMERCIALLY APPLICABLE - BUKIN DAULAY; BINARKO SANTOSO; IKIN SODIKIN (Indonesian Mining Journal, 2007)
Low rank coal (LRC) that constitutes more than 65% of the national coal resources has to be utilized optimally in order to achieve the security of domestic energy supply and an optimum mix of primary energy consumption by the year 2025. The LRC can be upgraded to higher rank coal, both for export and domestic use, particularly for existing industries. Upgraded Brown Coal (UBC) process is one of the best upgrading technologies that can be implemented. Moreover, the low cost production of LRC and the availability of infrastructures would be the more attractive for UBC commercialization. Based on the coal quality specification recommended in this paper, the total moisture of the LRC varies from25.33 to 57.89% (typical 35 - 40%, as received/ar) and its calorific value ranges from 2,504 to 4,900 kcal/kg (typical 3,000 - 4,000 kcal/kg, ar). The ash content of the recommended LRC is less than 10% (typical <5%, dry basis/db) and the sulphur content is typical <0.5% (db). The LRC located in East and South Kalimantan is more attractive for UBC commercialization compared to LRC located in South Sumatera. Most of the LRC in South Sumatera is located far inland that makes the transporta- tion cost for UBC equipment and product become expensive.